Implementasi Paradigma Baru PAI dalam Penguatan Karakter Religius Peserta Didik di Era Kontemporer: Studi Kasus di MA Sunanul Huda Sukabumi - Fatimah, Euis Nur; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2026)
This study aims to analyze the implementation strategies of the new paradigm of Islamic Religious Education (PAI) in strengthening students’ religious character in the contemporary era. The method used is a qualitative approach with a case study design. Data were collected through in-depth interviews with PAI teachers and students, observations of learning activities and religious practices, as well as documentation of religious programs such as congregational prayers, Qur’an recitation, wirid practices, and classical Islamic book studies (kitab kuning). The results of the study indicate that the new paradigm of PAI is implemented through contextual and active learning, teacher role modeling, and habituation of worship practices supported by a pesantren culture. These strategies have a positive impact on strengthening students’ religious character, as reflected in improved discipline in worship, better moral behavior, and greater social awareness. The integration between classroom learning and religious practices outside the classroom creates a holistic educational environment. However, challenges remain, including the influence of social media and students’ consistency in applying religious attitudes outside the school environment. Overall, the new paradigm of PAI has proven effective in addressing contemporary educational challenges.